2015
DOI: 10.2147/jpr.s79618
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonrecurring alcohol administration on pain perception in humans: a systematic review

Abstract: PurposeAlcohol is believed to have pain-dampening effects and is often used as self-medication by persons with pain problems; however, experimental evidence confirming this effect is scarce. We conducted a systematic review of experimental studies on the effects of nonrecurring alcohol administration on pain perception in healthy human subjects and the underlying mechanisms.MethodThree databases (PubMed, PsycINFO, and Web of Science) were searched for relevant studies using a predefined algorithm. In a next st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 56 publications
(107 reference statements)
1
25
0
1
Order By: Relevance
“…We aimed to avoid important factors known to influence pain sensation, such as exhaustion, strenuous physical activity, alcohol, and drug abuse. Furthermore, we gave strict instructions to the subjects concerning avoiding alcohol and changes in physical activity patterns during the time of study and to get enough sleep . There may of course be other influencing factors that we did not adjust for.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to avoid important factors known to influence pain sensation, such as exhaustion, strenuous physical activity, alcohol, and drug abuse. Furthermore, we gave strict instructions to the subjects concerning avoiding alcohol and changes in physical activity patterns during the time of study and to get enough sleep . There may of course be other influencing factors that we did not adjust for.…”
Section: Discussionmentioning
confidence: 99%
“…A survey in Pakistan on the treatment of headache with 248 respondents showed that unprescribed pharmaceutical drugs (87.1%) were the most common treatment approach, whereas vitamins (3.4%), massage (4.5%), herbal remedies (2.2%), and homeopathic medicines (2.8%) were also adopted ( 6 ). Additionally, alcohol has been found to have pain-dampening effects, although the mechanism is unclear ( 31 , 32 ). Other diseases with high self-medication prevalence include malaria ( 33 35 ), psoriasis ( 36 , 37 ), oral disease ( 38 ), ophthalmology ( 39 ), and COPD ( 40 ).…”
Section: Prevalence Of Self-treatmentmentioning
confidence: 99%
“…In fact, the anesthetic and analgesic properties of alcohol have been recorded for centuries and alcohol is frequently used as self-medication in pain syndromes. [88,89] Some experiments show that alcohol have analgesic effect in the early hours after their administration, which is the amount of time ADs have been reported to trigger MO, MA, and CH. In fact, rats that received dural stimulation followed by alcohol showed an initial analgesic effect within the first 2 h after alcohol ingestion; however, 4-6 h later, their pain sensitivity increased.…”
Section: Th % M %mentioning
confidence: 99%